Abuse of peer review process by sham authors - T., Senthil Kumar; Sorooshian, Shahryar (European Association of Science Editors (EASE), 2020)
This is a short letter on how the peer review process of many journals is being abused by some sham authors. While it would be difficult for the journals to identify and eliminate manuscripts that are not submitted with a sincere intention to publish, the universities and learning institutions should develop code of ethics to prevent their staff from abusing the journal review process. Imposing submission fee would also act as a deterrent against unscrupulous submissions.